Improving Student Learning Outcomes by Using Student Worksheets in Islamic Education Learning: Classroom Action Research at State Senior High School 15 Padang - Yetti, Zulafni (DARUSSALAM: Scientific Journal of Islamic Education, 2024)
This study aims to improve student learning outcomes in Islamic religious education learning by using student worksheets. This study is a classroom action research that uses four steps, namely planning, action, observation and reflection. The subjects of this study were high school students. The data for this study were obtained by test and observation techniques. Tests are used to measure learning outcomes and observations are used to analyze teacher and student learning activities. The data analysis technique used in this study is descriptive statistics. The results of the study indicate that student worksheets can improve student learning outcomes in Islamic religious education learning. Thus, the use of student worksheets can be used as an alternative to improve student learning outcomes in Islamic religious education learning